2020
DOI: 10.1093/ajh/hpaa142
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and Increased Permeability Over the Blood–Brain Barrier: A Role of Vascular Endothelial Growth Receptor 2

Abstract: BACKGROUND Cerebral complications in preeclampsia are leading causes of maternal mortality worldwide but the underlying pathophysiology is largely unknown and a challenge to study. Using an in vitro model of the human blood brain barrier (BBB), we explored the role of vascular endothelial growth factor receptor 2 (VEGFR2) in preeclampsia. METHODS The human brain endothelial cell line (hCMEC/D3) cultured on Tranwells insert we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…In the context of preeclampsia, a study demonstrated that plasma from preeclamptic pregnancies increased the permeability of cerebral rat veins (Amburgey et al, 2010), being this effect counteracted by co-treatment with a VEGFR2 inhibitor. The above outcome is confirmed in human hCMEC/d3 cells, as plasma from preeclamptic pregnancies, apart from increasing the permeability, up-regulated the mRNA expression of VEGFR2 and phosphorylation at the tyrosine residue Y951 (pY951), along with a decreased phosphorylation at the Y1175 (pY1175) residue (Bergman et al, 2021). The above findings agree with those that relate the pY951 with increased endothelial permeability (Matsumoto et al, 2005).…”
Section: Overview Of Vegf Signaling and Its Role On The Cerebrovascul...supporting
confidence: 84%
See 1 more Smart Citation
“…In the context of preeclampsia, a study demonstrated that plasma from preeclamptic pregnancies increased the permeability of cerebral rat veins (Amburgey et al, 2010), being this effect counteracted by co-treatment with a VEGFR2 inhibitor. The above outcome is confirmed in human hCMEC/d3 cells, as plasma from preeclamptic pregnancies, apart from increasing the permeability, up-regulated the mRNA expression of VEGFR2 and phosphorylation at the tyrosine residue Y951 (pY951), along with a decreased phosphorylation at the Y1175 (pY1175) residue (Bergman et al, 2021). The above findings agree with those that relate the pY951 with increased endothelial permeability (Matsumoto et al, 2005).…”
Section: Overview Of Vegf Signaling and Its Role On The Cerebrovascul...supporting
confidence: 84%
“…Findings from these studies generally agree that preeclamptic women may suffer some degree of cerebrovascular damage. Recent studies published by our group showed that exposure of hCMEC/d3 cell monolayers (a human brain endothelial cell line) to plasma from preeclamptic pregnancies increased permeability to FITC-dextran 70 kDa and reduced their transendothelial electrical resistance ( Bergman et al, 2021 ; Leon et al, 2021 ), with no changes in tight junction proteins mRNA expression ( Bergman et al, 2021 ).…”
Section: The Blood-brain Barrier In Preeclampsiamentioning
confidence: 99%
“…Our group previously reported on in vitro studies of the human brain endothelium, exposed to plasma from women with preeclampsia [ 24 ]. We demonstrated increased permeability and a lower trans endothelial electrical resistance over the in vitro blood–brain barrier after exposure to plasma from women with preeclampsia compared to normotensive women, implicating that plasma from women with preeclampsia induces injury to the blood–brain barrier [ 24 ], supporting the findings from animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmatory experiments of TEER and cell permeability to high-molecular weight fluorescent dye (Fluorescein-5-isothiocyanate FITC-dextran 70 kDa) were performed as previously reported [ 30 ] using randomly selected plasmas from women with preeclampsia (n = 12), and women with normal pregnancies (n = 13).…”
Section: Methodsmentioning
confidence: 99%
“…Up until recently there has been a paucity of studies assessing the human BBB in preeclampsia, due to difficulties in studying the BBB in a clinical setting. However, our research group has recently presented promising results on the human cerebral microvascular endothelial cell line (hCMEC/D3) [ 27 , 28 , 29 ] as a new in vitro model of the BBB in preeclampsia research [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%